2003
DOI: 10.1128/jcm.41.8.3706-3711.2003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Bordetella pertussis and Bordetella parapertussis Isolates Circulating in Saint Petersburg between 1998 and 2000 with Russian Vaccine Strains

Abstract: We analyzed the Bordetella pertussis and Bordetella parapertussis isolates circulating in Saint Petersburg that were collected between 1998 and 2000 and compared them with isolates collected 40 years ago and Russian vaccine strains. The analysis involved serotyping, pulsed-field gel electrophoresis of chromosomal DNA after digestion with XbaI and SpeI, and sequencing of the ptxS1 and prn genes, which encode the S1 subunit of the pertussis toxin and the major adhesin pertactin, respectively. The Russian isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…However, it is important to note that pursuing culture is essential in order to analyze the spatio-temporal evolution of Bordetella pertussis according to the immunity of the human population. We observed that the collected isolates were very similar to each other (all PFGE group IV), confirming our previous results obtained in Argentina (4), Europe (7), Japan (14), Russia (17), and France (6,26). We demonstrated that the PFGE group IV subgroup gamma, first observed in Finland and more recently in France (5, 7), is now also circulating in the United States.…”
Section: Discussionsupporting
confidence: 80%
“…However, it is important to note that pursuing culture is essential in order to analyze the spatio-temporal evolution of Bordetella pertussis according to the immunity of the human population. We observed that the collected isolates were very similar to each other (all PFGE group IV), confirming our previous results obtained in Argentina (4), Europe (7), Japan (14), Russia (17), and France (6,26). We demonstrated that the PFGE group IV subgroup gamma, first observed in Finland and more recently in France (5, 7), is now also circulating in the United States.…”
Section: Discussionsupporting
confidence: 80%
“…Researchers point to many reasons for the increased incidence of pertussis, including improved surveillance, waning immunity, and pathogen adaptation. The last possibility is supported by the fact that divergence in the protective antigens pertussis toxin (Ptx) and pertactin (Prn) has been observed between vaccine strains and the strains circulating in many countries (2,7,9,12,13,17,18,20,24,(31)(32)(33). In general, it was found that "non-vaccine-type" alleles of ptxA and prn (i.e., ptxA1, prn2, and prn3) have gradually replaced the "vaccinetype" alleles (i.e., ptxA2, ptxA4, and prn1) that were in circulation earlier.…”
mentioning
confidence: 94%
“…In general, it was found that "non-vaccine-type" alleles of ptxA and prn (i.e., ptxA1, prn2, and prn3) have gradually replaced the "vaccinetype" alleles (i.e., ptxA2, ptxA4, and prn1) that were in circulation earlier. Analysis of strains isolated in Russia (Moscow and St. Petersburg) from 1998 to 2002 also revealed that strains with the ptxA1 and the prn2 or prn3 alleles prevailed in circulation (12,14). Possible variations in nucleotide sequences in 15 other genes encoding surface-exposed proteins have also been studied.…”
mentioning
confidence: 99%
“…Since Mooi et al (20) found that the circulating clinical strains had antigens distinct from those of vaccine strains, they proposed that the circulating clinical strains might have escaped the immunity provided by pertussis vaccination. The antigenic divergence between recently circulating strains and vaccine strains has been reported in European and North American countries (3,6,9,16,19,22,(29)(30)(31) but not in Asian countries.…”
mentioning
confidence: 99%